2022
DOI: 10.3390/ijerph192114129
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Comprehensive, General Health Literacy in the General Adult Population: The Development and Validation of the HLS19-Q12 Instrument in Seventeen Countries

Abstract: Background: For improving health literacy (HL) by national and international public health policy, measuring population HL by a comprehensive instrument is needed. A short instrument, the HLS19-Q12 based on the HLS-EU-Q47, was developed, translated, applied, and validated in 17 countries in the WHO European Region. Methods: For factorial validity/dimensionality, Cronbach alphas, confirmatory factor analysis (CFA), Rasch model (RM), and Partial Credit Model (PCM) were used. For discriminant validity, correlatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 59 publications
(66 reference statements)
4
28
1
Order By: Relevance
“…The European Health Literacy Population Survey 2019-2021 (HLS 19 -Q12) was used to measure teachers’ personal health literacy (14). The HLS 19 -Q12 is a 12-item instrument to assess personal health literacy and was developed by the WHO Action Network on Measuring Population and Organizational Health Literacy (M-POHL) working group.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The European Health Literacy Population Survey 2019-2021 (HLS 19 -Q12) was used to measure teachers’ personal health literacy (14). The HLS 19 -Q12 is a 12-item instrument to assess personal health literacy and was developed by the WHO Action Network on Measuring Population and Organizational Health Literacy (M-POHL) working group.…”
Section: Methodsmentioning
confidence: 99%
“…The total score of the HLS 19 -Q12 was calculated as the percentage (ranging from 0 to 100) of items with valid responses that were answered with “very easy” or “easy” provided that at least 80% of the items contain valid responses (14). If less than 80% of the items contain valid responses, the score was coded as “missing.” Higher scores of the HLS 19 -Q12 indicate higher levels of health literacy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surveys carried out in numerous nations indicated that people's levels of HL were inadequate. According to studies conducted in the United States and 17 European countries, 88% and 46% of people were found to have inadequate HL, respectively (13,14). Furthermore, 80% of Turks were found to have inadequate HL (15).…”
Section: Introductionmentioning
confidence: 99%